cis- and trans-Acting Elements Involved in Regulation of aniA, the Gene Encoding the Major Anaerobically Induced Outer Membrane Protein in Neisseria gonorrhoeae - Householder, Tracey C. (American Society for Microbiology, 1999)
AniA (formerly Pan1) is the major anaerobically induced outer membrane protein in Neisseria gonorrhoeae. AniA has been shown to be a major antigen in patients with gonococcal disease, and we have been studying its regulation in order to understand the gonococcal response to anaerobiosis and its potential role in virulence. This study presents a genetic analysis of aniA regulation. Through deletion analysis of the upstream region, we have determined the minimal promoter region necessary for aniA expression. This 130-bp region contains a sigma 70-type promoter and an FNR (fumarate and nitrate reductase regulator protein) binding site, both of which are absolutely required for anaerobic expression. Also located in the minimal promoter region are three T-rich direct repeats and several potential NarP binding sites. This 80-bp region is required for induction by nitrite. By site-directed mutagenesis of promoter sequences, we have determined that the transcription of aniA is initiated only from the sigma 70-type promoter. The gearbox promoter, previously believed to be the major promoter, does not appear to be active during anaerobiosis. The gonococcal FNR and NarP homologs are involved in the regulation of aniA, and we demonstrate that placing aniA under the control of the tac promoter compensates for the inability of a gonococcal fnr mutant to grow anaerobically.